Introduction to agronomy and soil and water management - Vaidya V.G. & Sahasrabuddhe K.R. (Anmol prakashan, Pune, 1996)
Dry-land Agriculture
ENGLISH
Keywords: Introduction to agronomy and soil and water management; Dry-land Agriculture; Dry-land Agriculture